Makanan Tumpeng dalam Tradisi Bancakan - M. Zein Ed-Dally; Nur Faizah (Qurthuba: The Journal of History and Islamic Civilization, 2020)
Abstract: The lack of culinary treasures in our historical literature is the background of this research. Therefore, this study aims to find out the history and philosophy of Tumpeng in the tradition of pre-Islamic Javanese society and to understand the development of Tumpeng in the bancakan tradition of Javanese society after the arrival of Islamic influence. This study uses historical (historical) research methods which include heuristic methods, source verification, text interpretation, and historiography, as well as using a gastronomic approach. Apart from that, this study also uses the theory of symbolic culture based on Clifford Geertz's version as a tool for historical analysis. The results of this study found several historical facts, namely: 1) Tumpeng is a food that has existed since the Javanese people still embraced the Kapitayan belief, which is served and offered as a means to worship "God" which they believe is something that cannot be explained and cannot be reached by the five senses, or better known as Sang Hyang Tunggal. 2) After the Hindu-Buddhist influence entered and took root firmly in the beliefs of the Javanese people, the shape of Tumpeng began to change into a cone (mountain). 3) After the spread of Islam carried out by Walisongo through a process of assimilation and syncretization of culture which was previously thick with the teachings of Kapitayan and Hindu-Buddhist beliefs into a culture that has internalized Islamic values, Tumpeng automatically also experiences a shift in values. Keywords: Tumpeng, Bancakan, Java, Islam